Potential Probiotic Properties of Exopolysaccharide-Producing Lacticaseibacillus paracasei EPS DA-BACS and Prebiotic Activity of Its Exopolysaccharide - Min-Gyu Lee; Huijin Joeng; Jaein Shin; Suin Kim; Chaeeun Lee; Youngbo Song; Byung-Hoo Lee; Hyoung-Geun Park; Tae-Ho Lee; Hai-Hua Jiang; Young-Sun Han; Bong-Gyeong Lee; et al. (Microorganisms, 2022)
Exopolysaccharide (EPS)-producing Lacticaseibacillus paracasei EPS DA-BACS was isolated from healthy human feces and its probiotic properties, as well as the structure and prebiotic activity of the EPS from this strain were examined. EPS from L. paracasei EPS DA-BACS had a ropy phenotype, which is known to have potential health benefits and is identified as loosely cell-bounded glucomannan-type EPS with a molecular size of 3.7 × 106 Da. EPS promoted the acid tolerance of L. paracasei EPS DA-BACS and provided cells with tolerance to gastrointestinal stress. The purified EPS showed growth inhibitory activity against Clostridium difficile. L. paracasei EPS DA-BACS cells completely inhibited the growth of Bacillus subtilis, Pseudomonas aeruginosa, and Aspergillus brasiliensis, as well as showed high growth inhibitory activity against Staphylococcus aureus and Escherichia coli. Treatment of lipopolysaccharide-stimulated RAW 264.7 cells with heat-killed L. paracasei EPS DA-BACS cells led to a decrease in the production of nitric oxide, indicating the anti-inflammatory activity of L. paracasei EPS DA-BACS. Purified EPS promoted the growth of Lactobacillus gasseri, Bifidobacterium bifidum, B. animalis, and B. faecale which showed high prebiotic activity. L. paracasei EPS DA-BACS harbors no antibiotic resistance genes or virulence factors. Therefore, L. paracasei EPS DA-BACS exhibits anti-inflammatory and antimicrobial activities with high gut adhesion ability and gastrointestinal tolerance and can be used as a potential probiotic.